Word Formation of Photography Terminologies - Akhmad Multazim; Ermayni Sari Nurdin (Universitas Sanata Dharma, 2019)
Technology and social media affected the use of word as part of language in certain domain as a means of communication. The research objectives were to find out the types of word formation, the dominant type and the reason of dominancy of word formation of photography terminologies in online magazine outdoorphotographer.com. It was a descriptive qualitative research concerning on exploring language particularly on word level. Data were collected from articles published on online magazine from January to August 2018 by reading, note-taking and check-listing. To analyze the types of word formation, a theory by Stockwell and Minkova was used and to analyze the meaning of the terminologies, Cambridge and Oxford dictionaries were used. The result showed that there were 198 photography terminologies found. These terminologies were classified into six types of word formation, namely acronym (12 data), borrowing (3 data), compounding (166 data), clipping (3 data), derivation (3 data) and eponym (1 datum). The most dominant type was compounding. It was very dominant due to its simplicity to form a new word by simply combining two or more words without any change of its elements. This research revealed many photography terminologies that could be used to enrich vocabularyKeywords: Word formation, Photography terminologies, Outdoorphotographer.com